(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
Chinese script is the language with the largest number of speakers today, and the language is gaining popularity. The writing of this language is based on hieroglyphs, and its formation goes back to the distant past. Let’s take a brief look at the development of this language